Responses to growth hormone (GH) therapy in short children with normal GH secretion and no bone age delay: an analysis of potential factors affecting their response to rhGH therapy. A controlled study - Soliman, Ashraf T; Elawwa, Ahmed; Itani, Maya; Jour, Celine; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Variability still exist about the growth response to growth hormone (GH) therapy in children with idiopathic short stature (ISS). We describe the growth response to rhGH therapy for >2 years in 20 prepubertal children with idiopathic short stature (ISS) and 18 children with GH deficiency (GHD) and compared them with 15 children with ISS who did not receive rhGH therapy. Patients and methods: Our study included 35 prepubertal and peripubertal (Tanner 1 and 2) children with short stature (Ht-SDS <-2) and/or Ht-SDS >1SD below their mid parental height SD (MP-Ht-SDS) with slow growth velocity (<-1 SD), with normal peak GH response to provocation tests (15.5±6.5 ng/dl), normal IGF-I SDS (-0.9±0.6), and no bone age delay (± 1 year from chronological age) (ISS). 20 children were treated for 2.5±1.5 years with rhGH 0.05 mg/kg/day and 15 children were not treated with rhGH. 18 children with diagnosis of GHD, diagnosed in the same period, receiving rhGH therapy served as controls. We assessed the linear growth and IGF-I levels of all children for an average of 2 years. Results: Children with ISS on rhGH therapy had a height gain of 0.77 SD in 2 years versus 1.05 SD in GHD children, with significant increase in IGF-I and normal progression of bone age and puberty. Children with ISS who did not receive rhGH had no gain in the changes of Ht-SDS inspite of normal progression of bone age and puberty. The difference between children Ht-SDS and mid-parental height SDS (MP-Ht-SDS) changed significantly from -1.1±3 to -0.3±0.5 in the ISS group and from -1.35±0.5 to -0.3±0.25 in the GHD group, after an average of 2 years of treatment. In the treated ISS group, the Ht-SDS gain was correlated positively with the duration of rhGH therapy (r = 0.82, p<0.0001), negatively with the age at the start of treatment (r = -0.544, p = 0.01), and positively with the bone age (r =-0.44, p = 0.04). Discussion: The Ht-SDS of children with ISS on rhGH treatment closely approached their MP-Ht-SDS after 2 years of rhGH therapy while those who did not receive rhGH kept the same distance from their MP-Ht-SDS after 2 years. Analysis of possible factors affecting linear growth in children with ISS on rhGH therapy showed that children below 9 years with Ht-SDS <-2.5 SD and those with Ht-SDS >1SD below MP-Ht-SDS grew better on rhGH therapy compared to older children and those with Ht-SDS >-2.5 and were less than 1SD from their MP-HT-SD. Higher doses of rhGH (to keep IGF-I in high normal levels) and longer duration of therapy improved the Ht-SDS gain of these children. Conclusion: We report significant gain in Ht-SDS in prepubertal children with ISS on rhGH therapy and better response in younger children and in those with Ht-SDS > 1 SD below their MP-Ht-SDS.